EFFECTS OF SURFACE ACTIVE SUBSTANCES IN PROTECTION OF DRY COCOON FROM DUST AND OTHER FACTORS (Archive of Conferences, 2020)
In the article given the results of modification with the chemical preparate SFM for saving silk’s natural appearance and characters in the silk industry